Pengembangan Agrowisata Pesuteraan Alam Sutera Sari Segara di Desa Sibangkaja, Kecamatan Abiansemal - Effendi, Rahmat; Narka Tenaya, I Made; Sudarma, I Made (JURNAL MANAJEMEN AGRIBISNIS (Journal Of Agribusiness Management), 2015)
One alternative destination agrotourism in Bali is Agrowisata Pesuteraan alam Sutera Sari Segara located in the village Sibangkaja , District Abiansemal. The agrotourism is a potential to be developed in the world of tourismin Bali . Market segmentation is still dominated by 99 percent students are very massive factor in the development of the market in Bali . The purpose of this study was to determine the diversity of the work done by agrotourism , internal and external factors that influence the development of agrotourism , and alternative development strategies and priorities in agrotourism. Respondents in this study were dividedin to two , namely the respondent's internal and external respondents . Internal respondents were employees of agrotourism taken by census and external respondents that visitors and government who have a relationship with agrotourism . The results of research to get 5 alternative strategies witheach priorityi san alternative way of running the promotion of agrotourism by way of advertising and media selection through brochures , synergy between agrotourism and stakeholders by way of synergy between agrotourism with the private sector , the expansion of market segments using market segmentation way , improving the quality of HR by way of provision of qualified work force , and the quality of agrotourism attractions and silk fabric by settin gquality standards . Suggestions that cangive authors in this study is the use of alternative strategies and priorities that are used to further develop agrotourism . Alternative promotion of agrotourism means of advertising that holds the highest value can be used to developth is agrobusiness. Selection of media for advertising such as brochures media is the most efficient and effective way to convey information to tourists or potential tourists.
Keywords: agrowisata, pesuteraan alam agrowisata pesuteraan